2020
DOI: 10.3390/nu12082227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Nitrate Supplementation on Weightlifting Exercise Performance in Healthy Adults: A Systematic Review

Abstract: Dietary nitrate (NO3−) supplementation has been evidenced to induce an ergogenic effect in endurance and sprint-type exercise, which may be underpinned by enhanced muscle contractility and perfusion, particularly in type II muscle fibers. However, limited data are available to evaluate the ergogenic potential of NO3− supplementation during other exercise modalities that mandate type II fiber recruitment, such as weightlifting exercise (i.e., resistance exercise). In this systematic review, we examine the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 153 publications
(269 reference statements)
2
16
0
1
Order By: Relevance
“…This is the first systematic review and meta-analysis evaluating the effects of dietary NO 3 − supplementation on maximal neuromuscular power in humans, and also the first individual participant data meta-analysis of the effects of dietary NO 3 − on any aspect of human performance. Our primary finding is that NO 3 − intake significantly enhances muscle power, thus supporting the conclusions of previous narrative reviews [14,17]. This effect was statistically independent of subject age or sex and was evident during both small and large muscle Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is the first systematic review and meta-analysis evaluating the effects of dietary NO 3 − supplementation on maximal neuromuscular power in humans, and also the first individual participant data meta-analysis of the effects of dietary NO 3 − on any aspect of human performance. Our primary finding is that NO 3 − intake significantly enhances muscle power, thus supporting the conclusions of previous narrative reviews [14,17]. This effect was statistically independent of subject age or sex and was evident during both small and large muscle Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The present meta-analysis lends quantitative support to previous narrative reviews [14,17] that have concluded that NO 3 − supplementation enhances maximal neuromuscular power in humans. Based on the currently available literature, this ergogenic effect is seemingly independent of subject age, sex, or the amount of muscle mass engaged in the activity but may be greater with acute vs. repeated dosing.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, supplementation with B-alanine increases muscle carnosine synthesis, favouring the regulation of the acid–base balance at the intramuscular level and enhancing muscle contractility [ 77 , 78 , 79 ]), its ergogenic effect on efforts with a high glycolytic component having been demonstrated [ 80 , 81 ], while sodium bicarbonate (due to an improvement in the regulation of extracellular pH and the consequent delay in fatigue) [ 82 , 83 ]) has an ergogenic effect in intermittent endurance tests [ 84 ] and muscular endurance [ 85 ]. On the other hand, supplementation with beet juice is a nutritional source rich in nitrate that can increase the bioavailability of nitric oxide, improving the performance of muscle strength [ 86 ], endurance capacity [ 87 ] and intermittent high- intensity efforts [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some research, however, focuses on investigating these effects on high-intensity exercise and strength, where mixed results are observed. Thompson et al (2016) − on upper body strength and the number of repetitions performed in upper body strength test (bench press) as well as lower body strength test (squat) [92]. We certainly need more research into the impact of NO 3 − on high-intensity exercise and strength, but preliminary results suggest that NO 3 − could be beneficial in this sport context as well.…”
Section: Nitrates: Effects Of Exercise Type and Conditionsmentioning
confidence: 99%